On classification of 5-dimensional solvable Leibniz algebras - Khudoyberdiyev, Abror Khakimovich; Sattarovich, Rakhimov Isamiddin; Said Husain, Sharifah Kartini (Elsevier, 2014)
In the paper we describe 5-dimensional solvable Leibniz algebras with three-dimensional nilradical. Since those 5-dimensional solvable Leibniz algebras whose nilradical is three-dimensional Heisenberg algebra have been classified before we focus on the rest cases. The result of the paper together with Heisenberg nilradical case gives complete classification of all 5-dimensional solvable Leibniz algebras with three-dimensional nilradical.